EFFECTIVE APPROACHES TO TEACHING THE TOPIC “CHEMICAL REACTION RATE” BASED ON THE PRINCIPLES OF SUSTAINABLE DEVELOPMENT - Islomova Iroda Ozod qizi,; Ataullayev Zokir Makhsudovich,; Eshchanov Ruzumboy Abdullayevich, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Today, integrating the principles of sustainable development into the educational process is considered one of the urgent tasks of the education system. Sustainable development implies not only economic and social progress, but also the preservation of ecological balance. In this regard, teaching chemistry plays an important role in promoting environmental protection, the rational use of natural resources, and the formation of ecological culture.